Faktor-Faktor yang Berhubungan dengan Pemberian ASI Eksklusif di Puskesmas Beru-Beru Kalukku Kabupaten Mamuju Sulawesi Barat - Satriani G.; Ashriady Ashriady; Dina Mariana (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2019)
In the WHO study of 3,000 times, breast milk contained all the nutrients needed by babies to survive at 6 months, starting with hormone antibodies, immune factors, and antioxidants. The 2010 National Socio-Economic Survey data showed that only 33.6% of infants in Indonesia were breastfed, the 2013 Riskesdas data showed that the percentage of infants who gave birth exclusively to 6-year-olds was 38.0%. In 2016, urging Exclusive ASI in Mamuju District 30.3%, pushing the highest in Botteng Health Center, Simboro District and 3 Subdistricts with the lowest increase at Buttuada Health Center, Buttuada Subdistrict 8.9%, Beru-Beru Health Center Kalukku District 7.5% and Puskesmas Karama District Kalumpang 0%. The purpose of the study was to determine the factors associated with exclusive breastfeeding in Beru-Beru Health Center, Mamuju Regency, West Sulawesi. This type of research is observational with a cross sectional study design. Time of study in July - November Year Population is mothers who have ages 7 - 12 months in the work area of Beru-Beru Health Center, the study sample was taken using Total Sampling, the number of samples was 190 mothers. The results of this study indicate that there is a relationship between knowledge, attitudes, culture, the role of midwives, mother's work and IMD status with exclusive ASI assistance at Beru-beru Health Center. Exclusive breastfeeding at Beru-Beru Health Center. In the hypothesis of high risk, Exclusive breastfeeding for mothers who do not work, do IMD, have sufficient knowledge, good attitude and positive culture is 56%. The role of midwives in providing motivation, increasing knowledge of mothers, husbands and families is expected to improve the negative culture of exclusive breastfeeding and change the negative attitude of mothers about exclusive breastfeeding.